Job Insecurity in Selected Banks in Ibadan Southwest Nigeria - Adenugba, Adebimpe A.; Oteyowo, Odunayo (Richtmann Publishing, 2012)
Job insecurity has become an important phenomenon that affects the job performance. This problem is prominent isworsened in the banking sector of Nigeria. This paper examined Job Insecuity amongst bank workers in ten (10) selected newand old generation banks in Nigeria. The study was anchored on Adam Smith’s Equity theory, utilized both qualitative andquantitative techniques to gather data from two hundred and sixty (260) respondents randomly selected from the ten banks.Findings from the study revealed that Findings from the study showed that 58.8% of the respondents agreed that unfavorablegovernment policy makes their future uncertain and 55.2% agreed that absence of trade unions make the future of their jobunprotected. Also, 39.8% of the respondents have intention to leave their present employer and 54.4% agreed that there is highlabour turnover in their respective organizations. From the bivariate analysis, there was significant relationship between oldgeneration banks and new generation banks on perception of level of job insecurity (X2c=15.475; p<0.05; there was significantassociation between the age of respondents and perception on level of job insecurity (X2c=8.613; p<0.05); and there was nosignificant association between respondents’ category of staff and perception on level of job insecurity (X2c=0.009; p>0.05).Thepaper concluded that there is a high level of job insecurity among bank workers, especially those on contract appointment andrecommended : the need to harmonize the wage structure among both contract and permanent staff and to encourage tradeunionism in banks to protect the rights of workers